Field Monitoring and the Impact of Green Space on the Local Climate of Summer and Winter for the Duration (2023-2024) - al-Jabri, Mohammed Madloul Ayal; al-Mehaymid, Abdul Razak Khayoun Khadir (Journal of Ecohumanism, 2024)
The researcher divided the study area into seven key sectors, and identified in each sector two field monitoring sites for climate components: (temperature, humidity, wind speed and building temperature) using monitoring devices, and a field monitoring team was formed, and identified (14) monitoring field sites (7) within the green area and (7) Locations outside the green area, measured by the first two observations were the observation of the minimum temperature that began before sunrise, The second balances recorded in the afternoon for the great temperature, and the researcher chose the summer and winter seasons to see the differences in local climate elements, The study found out the differences between the elements of the local climate in the sectors of the study area, Edani recorded a degree of heat within the green area in the eastern Shamia sector in the inside and outside the green area and a difference between them (0.3 m °) The balances representing the maximum temperature were recorded by a difference between them. (2.1m °) While the sector recorded the highest temperature for the first micro-temperature balances inside and outside the area in the central sector by a difference (0.2 m °) The monitoring of the great temperature was recorded in and out of the green area by a difference (0.6 m °).